Disease risk assessment by clinical immunology analyses in periparturient dairy cows. (October 2015) - Amadori, M.; Fusi, F.; Bilato, D.; Archetti, I.L.; Lorenzi, V.; Bertocchi, L.
Abstract: A disease prediction system was investigated in a case–control study in the dry period of high-yielding dairy cows. Blood samples of 75 cows from 26 herds were collected before calving between − 23 and − 33 days (T1) and also between − 2 and − 6 days (T2) to investigate a panel of clinical immunology and chemistry parameters. Cows with abnormal serum lysozyme and interleukin-6 concentrations showed a greater disease prevalence until the 60th day in milk compared with non-responder cows (P < 0.05 and lower at T1). Differences in disease prevalence were observed on the basis of T1 data, and also by combining the results at T1 and T2. The other laboratory parameters under study were not predictive of a disease risk. Results indicate that environmental stressors in the dry period may cause a negative imprinting of the innate immune response, underlying predisposition to later disease occurrence. Highlights: A disease risk assessment procedure is proposed for dairy cows in the dry period. Risk assessment can be based on serum concentrations of lysozyme and interleukin-6. Abnormal values indicate a negative imprinting of innate immunity. Negative imprinting underlies predisposition to disease occurrence.